A36 Co-Developing a Shared Decision-Making Rubric for Peer-Evaluation in Simulation: Integrating Person-Centredness, Critical Reflection, and Collaborative Practice - Zainab Zahran; Aby Mitchell; John Brooks; Leanne Dolman; Victoria Clemett (Journal of Healthcare Simulation, 2025)
Introduction: Peer Evaluated Simulation (PES), embedded in a final-year undergraduate nursing module, enables students to enact clinical scenarios and receive formative feedback from peers. In simulation-based learning, peer evaluation can be a powerful formative assessment tool. Creating a rubric for peer evaluation in simulation is a structured approach that provides students with clear guidelines and criteria to assess their peers’ performance accurately and constructively [1,2]. A well-designed rubric standardises feedback, reduces subjective bias, and encourages reflective practice. The key concepts within this PES are related to Shared Decision Making (SDM), which is a neglected component of existing simulation rubrics. Therefore, this study outlines how these components are conceptualised and developed into the rubric to enable students to critically analyse each other’s performance in a constructive, respectful manner. Methods: A co-design educational approach, underpinned by a descriptive qualitative design was adopted. Three one- hour focus groups were conducted with final year nursing students, and standardised patients at a large UK university from February to June 2024 to iteratively co-design the content and implementation of the rubric. Focus groups were held over the MS-Teams platform and recorded. Thematic analysis was used to identify key aspects of SDM that informed and refined the rubric and its integration into a pre-registration nursing course. The study was guided by established programme theory on shared decision making [3]. Results: Several recurring themes emerged that informed the creation of the rubric: (1) patient-centred care and engagement; (2) communication skills; (3) team dynamics and interprofessional collaboration; (4) cultural competence and self-awareness; and (5) openness to learning. The co-development of this rubric ensured content validity for peer evaluators to rate and provide feedback on student’s shared decision-making behaviour in the simulation setting. Students positively evaluated the rubric’s clarity and relevance but highlighted the need for improved usability, clearer descriptors, and scenario specific alignment. Discussion: Findings demonstrate the feasibility and value of co-designing a SDM focused rubric for use in simulation-based nurse education. Involving students and patients in the design ensured alignment with authentic clinical experiences. Early introduction of the rubric into the curriculum, along with structured opportunities to practice giving feedback, were identified as essential. The rubric shows promise for supporting formative assessment and developing reflective practitioners. Future research should examine its reliability, potential for adaptation across settings, and integration into summative assessment strategies. Ethics Statement: As the submitting author, I can confirm that all relevant ethical standards of research and dissemination have been met. Additionally, I can confirm that the necessary ethical approval has been obtained, where applicable. References 1. Lertsakulbunlue S, Kantiwong N. Development of a peer-assessment rubric for nursing students in simulation-based learning. Journal of Nursing Education and Practice. 2024;14(2):10–16. doi: 10.1186/s41077-024-00301-7. 2. Panadero E, Jonsson A. The use of scoring rubrics for formative assessment purposes revisited: A review. Educational Research Review. 2013; 9:129–144. doi: 10.1016/j.edurev.2013.01.002. 3. Waldron T, Carr T, McMullen L, Westhorp G, Duncan V, Neufeld SM, Bandura LA, Groot G. Development of a program theory for shared decision-making: a realist synthesis. BMC health services research. 2020 Dec; 20:1–7. doi: 10.1186/s12913-019-4649-1. Acknowledgements/Funding Declaration: Funding: Florence Nightingale Faculty of Nursing, Midwifery & Palliative Care SeedCorn funding. Acknowledgments: We wish to thank all the participants in our study.